CHALLENGES FACED BY RURAL STUDENTS IN LEARNING ENGLISH - Khudoyorova Gulasal Ihomiddinovna. (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study explores the challenges faced by rural students in learning English, with a particular focus on the educational context of Uzbekistan. Despite the growing  importance  of  English  as  a  global  language  and  its  role  in  securing scholarships, employment, and international mobility, rural learners continue to face significant  barriers  to  effective  learning.  Using  a  combination  of  classroom observations,  personal  teaching  experience,  and  informal  interviews  with  rural students,  the  research  identifies  key  obstacles  such  as  limited  access  to  qualified teachers, outdated learning materials, inadequate exposure to real-life English use, and socio-economic constraints. In addition, cultural perceptions and traditional mindsets often  discourage  students,  particularly  girls,  from  fully  investing  in  English education.The findings call for targeted policy measures, improved teacher training, digital access, and community support programs to bridge the rural-urban gap.